2012
DOI: 10.1177/0363546512462124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abnormal Hip Findings in Asymptomatic Participants

Abstract: Magnetic resonance images of asymptomatic participants revealed abnormalities in 73% of hips, with labral tears being identified in 69% of the joints. A strong correlation was seen between participant age and early markers of cartilage degeneration such as cartilage defects and subchondral cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 29 publications
(39 reference statements)
2
105
1
2
Order By: Relevance
“…85 It is important to note that in 1 study, acetabular labral tears were present in 31 (69%) of 45 asymptomatic volunteers undergoing hip MRI. 86 The findings of this study underscore the importance of reconciling the clinical features of the patient with the imaging findings. In patients who cannot obtain an MRI examination, computed tomography arthrography is a suitable alternative for detection of labral tears, with sensitivity and specificity values comparable with those of MR arthrography.…”
Section: Anterior Hip Painmentioning
confidence: 61%
“…85 It is important to note that in 1 study, acetabular labral tears were present in 31 (69%) of 45 asymptomatic volunteers undergoing hip MRI. 86 The findings of this study underscore the importance of reconciling the clinical features of the patient with the imaging findings. In patients who cannot obtain an MRI examination, computed tomography arthrography is a suitable alternative for detection of labral tears, with sensitivity and specificity values comparable with those of MR arthrography.…”
Section: Anterior Hip Painmentioning
confidence: 61%
“…In 88 asymptomatic youth athletes, 65% had an alpha angle of greater than 55°and 70% had labral tears [21]. In a study of asymptomatic adults, we found that 95% of participants with FAI bony abnormalities (osseous bumps, fibrocystic changes of the femoral head/neck junction, and/or acetabular rim edema), had a labral tear [22]. The relationship between FAI and labral tears continues to be described.…”
mentioning
confidence: 78%
“…This view is supported by research showing that acetabular labral tears are present in a significant percentage of the asymptomatic population across a wide range of ages. 1,24,26 Patients with a labral tear observed on magnetic resonance arthrogram commonly have posterior-lateral hip pain that may originate from extra-articular structures. If treatment is directed at these extra-articular structures, the patient's symptoms could improve.…”
mentioning
confidence: 99%